Atrial High-Rate Episodes Detected by Cardiac Implantable Electronic Devices: Dynamic Changes in Episodes and Predictors of Incident Atrial Fibrillation - Imberti, Jacopo Francesco; Bonini, Niccolò; Tosetti, Alberto; Mei, Davide Antonio; Gerra, Luigi; Malavasi, Vincenzo Livio; Mazza, Andrea; Lip, Gregory Y. H.; Boriani, Giuseppe (Biology (Basel, Switzerland), 2022)
Background. Atrial high rate episodes (AHRE) detected by cardiac implantable electronic devices (CIEDs) may be associated with a risk of progression towards long-lasting episodes (≥24 h) and clinical atrial fibrillation (AF). Methods. Consecutive CIED patients presenting AHRE (with confirmation of an arrhythmia lasting 5 min–23 h 59 min, atrial rate ≥175/min, with no AF at 12-lead ECG and no prior clinical AF) were retrospectively enrolled. The aims of this study were to describe patients’ characteristics and the incidence of adverse events, and second, to identify potential predictors of the composite outcome of clinical AF and/or AHRE episodes lasting ≥24 h. Results. 104/107 (97.2%) patients (median age 79.7 (74.0–84.2), 33.7% female) had available follow-up data. Over a median follow-up of 24.3 (10.6–40.3) months, 31/104 (29.8%) patients experienced the composite outcome of clinical AF or AHRE episodes lasting ≥24 h. Baseline CHA2DS2-VASc score and the longest AHRE episode at enrollment lasting 12 h–23 h 59 min were independently associated with the composite outcome (Hazard ratio (HR); 95% CI: 1.40; 1.07–1.83 and HR: 8.15; 95% CI 2.32–28.65, respectively). Baseline CHA2DS2-VASc score and the longest AHRE episode at enrollment lasting 12 h–23 h 59 min were the only independent predictors of incident clinical AF (HR: 1.45; 95% CI 1.06–2.00 and HR: 4.25; 95% CI 1.05–17.20, respectively). Conclusions. In patients with AHRE, the incidence of clinical AF or AHRE episodes lasting ≥24 h is high in a two-year follow-up. Baseline patients’ characteristics (CHA2DS2-VASc score) and AHRE duration may help to intensify monitoring and decision-making, being independently associated with clinical AF at follow-up.